The Abortion Papers Ireland : Volume 2 - Conlon, Catherine; Kennedy, Sinead; Quilty, Aideen (Book collections on Project MUSE., 2016)
The Abortion Papers Ireland: Volume 2 is a unique edited collection that provides key reflections and scholarship from feminist academics and activists on ireland's abortion regime. this collection was prompted by the death of Savita Halappanavar in an irish hospital after being repeatedly denied a life-saving abortion in 2012. the broad-ranging and rich contributions reflect the period between the 1992 ‘X Case' judgement and the eventual introduction in 2013 of highly restrictive abortion legislation. Whilst a case study of ireland, the perspectives and analysis contained provide important insights and learning for broader, international reproductive justice debates and scholarship.